Fabricated silver nanoparticles by a combination of cell-free supernatant of Fusarium solani and Comamonas aquatica and its antibacterial activity (Sulaimani Journal for Pure and Applied Sciences, 2021)
The current study involves silver nanoparticles (AgNPs) synthesis, characterization, and antimicrobial activity of nanoparticles produced by a combination of cell-free supernatant (C-FS) of the intimate organisms, Fusarium solani and Comamonas aquatica as synthesis catalysts against Gram-negative and positive human pathogens. The detailed characterization of the Ag NPs was carried out using UV-visible spectroscopy, field emission Scanning Electron Microscopy (FE-SEM), transmission electron microscopy (TEM), and atomic force microscopy (AFM). From the UV-visible spectroscopy, the absorption peak was found at 442 nm, and FE-SEM images confirmed the formation of AgNPs. Further, TEM and AFM analysis demonstrated that fabricated AgNPs were relatively monodispersed, approximately spherical, and of the size between 2.0 - 7.5 nm. Furthermore, the antibacterial activity of AgNPs was determined by the agar well diffusion method, and results showed that AgNPs exhibited excellent antimicrobial activity against Gram-negative (E. coli, Pseudomonas aeruginosa, Salmonella enterica) and Gram-positive (Enterococcus faecalis and Staphylococcus aureus). Finally, The MIC test was performed to test the inhibitory concentration of AgNO3 against the bacteria under investigation. This is the first study proposing alternative sources to form AgNPs via synergistic metabolites of F. solani and C. aquatica. The results here offer a foundation for developing an effective therapy using AgNPs against various microorganisms which can endanger human beings.
Keywords: Sliver nanoparticles; Comamonas aquatica; Fusarium solani; Cell- free supernatant